Ultrafast charge transfer and recombination dynamics in monolayer–multilayer WSe2 junctions revealed by time-resolved photoemission electron microscopy - Xu, Ce (2024)
The ultrafast carrier dynamics of junctions between two chemically identical, but electronically distinct, transition metal dichalcogenides (TMDs) remains largely unknown. Here, we employ time-resolved photoemission electron microscopy (TR-PEEM) to probe the ultrafast carrier dynamics of a monolayer-to-multilayer (1L-ML) WSe2 junction. The TR-PEEM signals recorded for the individual components of the junction reveal the sub-ps carrier cooling dynamics of 1L- and 7L-WSe2, as well as few-ps exciton-exciton annihilation occurring on 1L-WSe2. We observe ultrafast interfacial hole (h) transfer from 1L- to 7L-WSe2 on an ∼0.2 ps time scale. The resultant excess h density in 7L-WSe2 decays by carrier recombination across the junction interface on an ∼100 ps time scale. Reminiscent of the behavior at a depletion region, the TR-PEEM image reveals the h density accumulation on the 7L-WSe2 interface, with a decay length ∼0.60 ± 0.17 μm. These charge transfer and recombination dynamics are in agreement with ab initio quantum dynamics. The computed orbital densities reveal that charge transfer occurs from the basal plane, which extends over both 1L and ML regions, to the upper plane localized on the ML region. This mode of charge transfer is distinctive to chemically homogeneous junctions of layered materials and constitutes an additional carrier deactivation pathway that should be considered in studies of 1L-TMDs found alongside their ML, a common occurrence in exfoliated samples.